Building Capacity for a Global Genome Editing Observatory: Institutional Design. Issue 8 (August 2018) - Saha, Krishanu; Hurlbut, J. Benjamin; Jasanoff, Sheila; Ahmed, Aziza; Appiah, Anthony; Bartholet, Elizabeth; Baylis, Françoise; Bennett, Gaymon; Church, George; Cohen, I. Glenn; Daley, George; Finneran, Kevin; et al.
Abstract : A new infrastructure is urgently needed at the global level to facilitate exchange on key issues concerning genome editing. We advocate the establishment of a global observatory to serve as a center for international, interdisciplinary, and cosmopolitan reflection. This article is the second of a two-part series.